The Vitamin D Binding Protein and Inflammatory Injury: A Mediator or Sentinel of Tissue Damage? - Kew, Richard R. (Frontiers in Endocrinology, 2019)
Neutrophils are the most abundant type of white blood cell in most mammals including humans. The primary role of these cells is host defense against microbes and clearance of tissue debris in order to facilitate wound healing and tissue regeneration. The recruitment of neutrophils from blood into tissues is a key step in this process and is mediated by numerous different chemoattractants. The neutrophil migratory response is essential for host defense and survival, but excessive tissue accumulation of neutrophils is observed in many inflammatory disorders and strongly correlates with disease pathology. The vitamin D binding protein (DBP) is a circulating multifunctional plasma protein that can significantly enhance the chemotactic activity of neutrophil chemoattractants both in vitro and in vivo. Recent in vivo studies using DBP deficient mice showed that DBP plays a larger and more central role during inflammation since it induces selective recruitment of neutrophils, and this cofactor function is not restricted to C5a, as prior in vitro studies indicated, but can enhance chemotaxis to many chemoattractants. DBP also is an extracellular scavenger for actin released from damaged/dead cells and formation of DBP-actin complexes is an immediate host response to tissue injury. Recent in vitro evidence indicates that DBP bound to G-actin, and not free DBP, functions as an indirect but essential cofactor for neutrophil migration. DBP-actin complexes always will be formed regardless of what initiated an inflammation, since release of actin from damaged cells is a common feature in all types of injury and DBP is abundant and ubiquitous in all extracellular fluids. Indeed, these complexes have been detected in blood and tissue fluids from both humans and experimental animals following various forms of injury. The published data strongly supports the premise that DBP-actin complexes are the functional neutrophil chemotactic cofactor that enhances neutrophil chemotaxis in vitro and augments neutrophilic inflammation in vivo. This review will assess the fundamental role of DBP in neutrophilic inflammation and injury.